2016
DOI: 10.1007/s00221-016-4586-8
|View full text |Cite
|
Sign up to set email alerts
|

Tactile stimulation during development alters the neuroanatomical organization of the optic nerve in normal rats

Abstract: This study was designed to investigate the progressive effect of tactile stimulation in the cytoarchitecture of the optic nerve of normal rats during early postnatal development. We used 36 male pups which were randomly assigned to either the tactile-stimulated group (TS-stimulation for 3 min, once a day, from postnatal day (P) 1 to 32) or the non-tactile-stimulated (NTS) group. Morphological analysis were performed to evaluate the alterations caused by tactile stimulation, and morphometric analysis were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
5
0
3
Order By: Relevance
“…In the rat, myelination in peripheral nerves is most rapid across the first 10 PNDs, compared with across PNDs 20–30 (Friede and Samorajski, ; Webster, ). In agreement with the present results, a recent study reported that tactile stimulation during the entire postnatal preweaning period increased oligodendrocyte density in the optic nerve (Horiquini‐Barbosa and Lachat, ) and prevent the iron‐deficiency disruption in oligodendrocytes and myelinated fiber density in the optic nerve (Horiquini‐Barbosa et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the rat, myelination in peripheral nerves is most rapid across the first 10 PNDs, compared with across PNDs 20–30 (Friede and Samorajski, ; Webster, ). In agreement with the present results, a recent study reported that tactile stimulation during the entire postnatal preweaning period increased oligodendrocyte density in the optic nerve (Horiquini‐Barbosa and Lachat, ) and prevent the iron‐deficiency disruption in oligodendrocytes and myelinated fiber density in the optic nerve (Horiquini‐Barbosa et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results coincide with a large body of work showing that early negative (complete maternal deprivation, early weaning or undernourishment), or positive (tactile and social stimulation) experiences modify myelination and the electrophysiological function of the CNS (Chatterjee et al, ; Kikusui et al, ; Ono et al, ; Horiquini‐Barbosa and Lachat, ; Antoniazzi et al, ) and the PNS (Segura et al, ; Segura et al, ; Quiroz‐González et al, ). Moreover, our results allow us to propose a discrete window of developmental time (PNDs 7–14), during which tactile stimulation normally exerts positive effects on myelination (Kikusui et al, ; Ono et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have demonstrated that TS is a model of positive early experiences in developing rats (Richards et al, ; Antoniazzi et al, ; Horiquini‐Barbosa and Lachat, ), exerting a solid influence on brain development (Chiba et al, ). In this regard, our current findings indicate that animals exposed to TS during the second week of life (PND8‐14) showed reduced anxiety‐like behavior, as observed by: (i) increased time spent in open arms of EPM, resulting in a lower anxiety index (AI) in this same paradigm; and (ii) reduction of their cumulative burying time in DBT, which is a type of strategy associated with the active behavior of burying shock probe (Matuszewich et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que o sistema nervoso responde de forma notável as interações com ambiente e isso pode moldar o seu desenvolvimento. Estudos têm mostrado mudanças nos processos bioquímicos, moleculares e na morfologia do desenvolvimento cerebral devido a estimulações ambientais, realizadas principalmente durante as fases precoces do desenvolvimento Kolb e Whishaw, 1998;Will et al, 2004;Horiquini-Barbosa e Lachat, 2016;Soares et al, 2017). Tem sido demonstrado que animais expostos a um ambiente enriquecido, que é uma combinação de estímulos sensoriais, sociais e físicos, pode levar a mudanças neuroanatômicas que diferem de animais que foram criados em condição padrão, além disso, os benefícios de um ambiente estimulante não se limitam às alterações morfológicas, mudanças comportamentais também são discutidas (Van Praag, Kempermann e Gage, 2000;Mohammed et al, 2002).…”
Section: Agradecimentosunclassified
“…A estimulação tátilestimulação sensorial da peleé considerada em ratos uma estimulação ambiental que mimetiza o cuidado materno, como o comportamento de lamber e o grooming, e em humanos pode ser entendida como uma estimulação sensorial da pele, como uma massagem. Esta estimulação também tem sido utilizada como modelo experimental para se estudar os mecanismos pelos quais variações precoces do ambiente afetam o desenvolvimento de sistema nervoso (Kolb e Gibb, 2007;Imanaka et al, 2008;Guzzetta et al, 2009;Gibb et al, 2010;Kolb e Gibb, 2010;Richards et al, 2012;Horiquini-Barbosa e Lachat, 2016). A estimulação tátil realizada em ratos no período pós-natal precoce, por meio do comportamento de lamber e de higiene fornecida pela rata lactante, influencia na estrutura e funcionalidade do cérebro, por meio de fatores de crescimento que são moléculas cruciais para a plasticidade cerebral, à exemplo disso, existem trabalhos que sugerem o Fator Neurotrófico Derivado do Cérebro (BDNF) e o Fator de Crescimento Neuronal (NGF), deste modo, a estimulação tátil realizada em laboratório por pesquisadores, parece utilizar mecanismos semelhantes de ação no sistema nervoso (Liu et al, 1997;Sale et al, 2004;Weaver et al, 2004).…”
Section: Agradecimentosunclassified